2012
DOI: 10.1177/1076029612463424
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Unfractionated and Low-Molecular-Weight Heparin on OPG, sRANKL, and von Willebrand Factor Concentrations During Hemodialysis

Abstract: Impact of heparin on endothelial cells and simultaneously on OPG/RANK/RANKL axis reinforces the presumption of the pathophysiological linkage between bone mineralization and endothelial dysfunction in end-stage renal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
8
1
Order By: Relevance
“…Although our results do not support the assumption that heparin could alter the production of OPG and RANKL, in clinical studies of hemodialysis patients [ 31 , 32 ] and healthy students [ 30 ], plasma levels of OPG and soluble RANKL were influenced by treatment with both heparin and low molecular weight heparin. There are two possible explanations for these inconsistent results.…”
Section: Discussioncontrasting
confidence: 99%
“…Although our results do not support the assumption that heparin could alter the production of OPG and RANKL, in clinical studies of hemodialysis patients [ 31 , 32 ] and healthy students [ 30 ], plasma levels of OPG and soluble RANKL were influenced by treatment with both heparin and low molecular weight heparin. There are two possible explanations for these inconsistent results.…”
Section: Discussioncontrasting
confidence: 99%
“…All the non-English articles were translated but did not meet criteria. Five studies were with a randomized cross-over design [16, 22, 24, 27, 29], nine were non-randomized cross-over [13–15, 17, 19–21, 25, 28] and three parallel design with randomization [18, 23, 26]. Two studies were excluded from the review since they reported the same results as studies included in the present review.…”
Section: Resultsmentioning
confidence: 99%
“…The OPG/RANKL system is involved in bone metabolism. No significant difference between LMWH and UFH (Additional file 2: Table S3) was found [16, 29]. Lai et al [20] measured the bone densitometry with dual energy X-ray and observed an increase of bone mass density (BMD) in ward’s triangle by 0.75% after switching to LMWH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, most high‐risk individuals received (multi‐)drug treatment. It has been demonstrated that in vivo treatment with antidiabetic medication,43, 44, 45, 46 statins,47, 48 heparins,49, 50 or glucocorticoids51 and in vitro treatment with irbesartan52 or different immunosuppressive therapies53 affect circulating osteoprotegerin levels. Second, circulating osteoprotegerin levels differ in people with preexisting diseases.…”
Section: Discussionmentioning
confidence: 99%